the 2nd International Conference on Material Engineering and Application selected, peer reviewed papers from the 2nd International Conference on Material Engineering and Application (2nd ICMEA 2017), August 18-20, 2017, Shanghai, China - Kaloop, Mosbeh (Applied mechanics and materials, 2018)
The objective of the 2nd International Conference on Material Engineering and Application (2nd ICMEA 2017, Shanghai, China, August 18-20, 2017) was to bring together academics, engineers, postgraduates and other professionals in the area of material science and engineering technology from many countries for the exchange of experience and discussion of the recent advances and the practical techniques in the field of materials science, mechanical engineering and manufacturing technologies. This book introduce to readers the newest research results in the field of material properties; materials testing and application in the mechanical engineering; newest experience in the engineering designing, materials manufacturing and processing technologies.